(untitled) (Journal of Laboratory Animal Science, 2021)
The use of animal models is critical to the biomedical research. Animals used for biomedical research should be in a state of absolute good health for reliable and reproducible results. It has been reported that infections,environmental factors, genetic factors and interactions of all these may influence the suitability of an animal for research.Sometimes, apparent healthy animals also suffer from latent infections. Majority of these infections are subclinical and may go undetected in gross examination, but clinical symptoms may appear under conditions of stress during experimentation. Also, it has been reported that even subclinical infections in rodents modify or alter research outcome. Many infectious agents affect results in the field of immunology, physiology, reproductive physiology, oncology and many more research areas. Hence, proper and periodic health monitoring programme is important to define the health status of experimental animals. In India, more than 1500 facilities are using laboratory animals for biomedical research. However, majority of them have not adopted the comprehensive health monitoring or disease diagnostic programme due to prohibitive cost of the diagnostic kits. Few facilities in India have adopted international guidelines in health monitoring/disease diagnosis and this includes conventional culture techniques, ELISA and PCR for rapid diagnosis. However, recent techniques such as MFI, Micro ELISA, Microarray and LAMP that have been developed and adopted elsewhere needs to be adopted in India for rapid and accurate diagnosis of pathogens in rodents.